Методи оцінювання кон’юнктури ринку автомобілебудівної продукції - Терлецька, В. О (Видавництво Львівської політехніки, 2015)
Досліджено підходи та методи оцінювання кон’юнктури ринку. Визначено, що оцінювання кон’юнктури ринку – надзвичайно складний та громіздкий процес, оскільки передбачає оцінювати не тільки стан ринку, його особливості і характер, а й чинники впливу на кон’юнктуру ринку. Проаналізовано існуючі методи оцінювання кон’юнктури ринку. Представлено характеристику підходів до оцінювання кон’юнктури ринку у табличній формі. Розглянуто і проаналізовано вказані підходи. Розроблено модель оцінювання кон’юнктури ринку, удосконалено та подано класифікацію показників кон’юнктури. In modern conditions of economic activity to the economic issues are particularly important to study methods of evaluation of market conditions, as they are extremely essential to obtain the current, objective and complete information concerning the state of the market. So the question about the role and importance methods of evaluation at present market conditions are particularly relevant. As the issue the evaluation of market conditions is one of the most difficult types of marketing research - covers an extensive range of issues in relation to choice and economic justification methods, techniques, methods of evaluation, indicators of market conditions, etc., and provides quantitative and qualitative (visual) assessment state of the market, trends of the development, nature and characteristics of the market, efficiency of functioning of enterprises in industry, economic situation in the market, determination ponderability of factors of market conditions, etc., and is aimed at the integral evaluation of economic performance in general - is an assessment of trends and patterns development of the market influenced by factors of market conditions. To achieve this goal the following objectives have been formulated. To achieve this goal required the following tasks: to investigate methods for evaluating market conditions; to analyse existing methods of assessment of market conditions; to investigate and improve of indicators of market conditions. The article explores the approaches and methods of the evaluation of market conditions. The author determines that the assessment of market conditions is an extremely complex and cumbersome process, that involves not only assess the state of the market, its features and character, but also factors of influencing the market conditions. Methods for evaluating the market conditions have been presented. Characterization of approaches to the evaluation of market conditions has been illustrated in tables. These approaches have been considered and analyzed. Model of the assessment of market conditions has been developed. Classification of indicators of market conditions has been represented and improved. The study of market trends, peculiarities of its operation, the nature and state of the market impacts, causation allows to explore, analyze and generate information and create analytical basis for determining priority research areas for the development of integrated methods for assessing the market conditions. In today’s researchers focused attention on the study of individual methods of evaluation of market conditions for specific sectors, while at the present stage of development necessary are essential integrated assessment methods that combine various combinations of existing techniques and allow systematically evaluate the market conditions, state of the industry and its character. Review of scientific literature [1-8] and studies of existing approaches to the assessment of the market conditions makes it possible to isolate and analyze two approaches to assessment. The first approach is to evaluate the market conditions in relation to evaluation of its condition through the use of universal methods of assessment, namely: economic and mathematical methods, statistical, empirical, expert and others. The second approach consists to assessment the factors of the market conditions that affect the market situation, and researcher is developing a method for evaluating, in which researcher defines the classification criteria and indicators for assessment (enterprise sector) independently and individually. This approach focuses on the use of a set of indicators that reflect the characteristics, nature, status and trends of the market conditions certain types of products (industry).
Methods of evaluation of the market conditions of automotive products
Keywords: кон’юнктуроутворювальні чинники; методи оцінювання; система показників кон’юнктури ринку; factors of market conditions; methods of evaluation; market conditions; system of indexes of the state of market conditions